2016
DOI: 10.1007/s10103-016-2059-8
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of prepared microgroove pattern by femtosecond laser on alumina-zirconia nano-composite for endosseous dental implant application

Abstract: Ceramic dental materials, especially alumina (20 %vol)-yttrium stabilized tetragonal zirconia poly crystal (A-Y-TZP20), have been considered as alternatives to metals for endosseous dental implant application. For increasing the bone-to-implant contact as well as the speed of bone formation, a new surface modification can be effective. The aim of this study was to design microgroove patterns by femtosecond laser on A-Y-TZP20 nano-composite disks for endosseous dental implant application. The phase composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 39 publications
0
10
0
2
Order By: Relevance
“…Aivazi et al also observed this on their experiments with alumina (20 %vol)-yttrium stabilized tetragonal zirconia poly crystal (A-Y-TZP20). The same fraction of monoclinic zirconia was found on the non-treated and laser treated specimens, concluding that the femtosecond laser did not alter the crystal structure of the ceramic [33].…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Aivazi et al also observed this on their experiments with alumina (20 %vol)-yttrium stabilized tetragonal zirconia poly crystal (A-Y-TZP20). The same fraction of monoclinic zirconia was found on the non-treated and laser treated specimens, concluding that the femtosecond laser did not alter the crystal structure of the ceramic [33].…”
Section: Discussionmentioning
confidence: 51%
“…Some authors have performed extensive material characterization on hard ceramics modified by femtosecond laser, aiming at dental implants applications [21,33,40]. On Zirconia, Stanciuc et al developed arrays of pits with different spacing, diameter and depth to evaluate human mesenchymal stem cells migration (hMSCs).…”
Section: Discussionmentioning
confidence: 99%
“…Модификация поверхности имплантатов важна для улучшения их остеоинтеграции [3,12,41,43,45,48,50,51].…”
Section: модификация поверхности изделия как фактор повышения эффектиunclassified
“…Некоторые методы лазерной обработки композитных материалов -A-Y-TZP20: тетрагональные поликристаллы циркония, стабилизиро-ванные алюминием (20 объемных %)-иттрием -значительно уменьшают содержание загрязнителей, таких как углерод, в поверхностных слоях по сравнению с таковым в конструкциях без воздействия лазером. Изучение изделий методом рентгеновской дифракции не выявило изменений кристаллической структуры, вызванных влиянием лазерной обработки [3].…”
Section: модификация поверхности изделия как фактор повышения эффектиunclassified
“…Femtosecond laser was used to machine dental ceramic implants made of zirconia-toughened alumina (ZTA) [18], or to induce regular patterns on an alumina-toughened zirconia (ATZ) surface [19]. And similarly to what was attempted in monolithic zirconia, laser-modifications of alumina-zirconia composites were used to induce osteogenic differentiation of human mesenchymal stem cells [20] and favour viability of osteoblast-like cells [21], or to help osseointegration of endosseous dental implants [22]. In addition to the microstructural changes induced in zirconia by the melting/ablation/quenching sequence, alumina-zirconia composites show also chemical changes, as reported by Ackerl et al [18] who reported that "Alumina […] seemed to dissolve approaching the surface".…”
Section: Introductionmentioning
confidence: 99%